Optimalisasi Potensi Pariwisata dan Lingkungan Melalui Program Pendidikan, Kesehatan, dan Pemberdayaan - Okid Parama Astirin; Setya Nugraha; Rahning Utomowati (LPPM UNS, 2020)
Buku Limau village is located at Belitung Timur district. This village is one out of 18 remoted villages which located in one region of Bangka Belitung Province. Buku Limau village is also one out of three villages which are populated by the people. One of the greatest potential of this village is tourism, which have a very lovey beaches all along the coast line. However, it seems that they do not have an adequate number of human resources. The purpose of this students community service programme is to increase the awereness of Buku Limau people in several important aspects, namely: education, tourism, well-being based on local wisdom. In order to increase those several aspects, the students will held several comunnity job, namely: first aid training, training and education for tourism human resources. These several community service will helped the people of Buku Limau to increase their wealth and boost the tourism programme.